Relationship between job factors and stress level among postgraduate Emergency Medicine trainees in Hospital Universiti Sains Malaysia - Thian, Lai Joon (2017)
Background Postgraduate residency training is a stressful process for physicians. Previous study in Malaysia showed 36.4% of postgraduate trainees experienced stress. Academic and performance pressure were the stressors among trainees. A stressful psychological condition may diminish job satisfaction and results in negative attitude towards work, interfere with intrapersonal and interpersonal relationship. Objective To study the relationship between job factors and stress level among Emergency Medicine Postgraduate trainees in Hospital Universiti Sains Malaysia (HUSM), Kelantan. Methodology A cross-sectional study was conducted in Emergency department, Hospital Universiti Sains Malaysia, Kelantan between the period of September 2014 till May 2016 and involving postgraduate Emergency Medicine trainees. Mean stress score was assessed using Depression, Anxiety, Stress Scale – 21 (DASS – 21) and job factors were evaluated using Job Content Questionnaire (JCQ). Simple linear regression and multiple linear regression analysis were used to determine the association of stress with job factors.Results A total of 61 postgraduate trainees were recruited for the study. Their mean stress score was 6.85  2.97. 39.3% of trainees experienced stress (22.9% mild stress, 11.5% moderate stress and 4.9% severe stress). Multiple linear regression showed age (p = 0.026), years of service (p = 0.015), skill discretion (p = 0.011) and psychological job demand (p = 0.044) has statistically significant association with stress. Conclusion More than half of the Emergency Medicine postgraduate trainees in Hospital Universiti Sains Malaysia experienced normal level of stress and 4.9% suffered severe stress. Age, year of service, skill discretion and psychological job demand were significantly associated with stress among postgraduate Emergency Medicine trainees.